Baby sleep incidental aspiration – case report - Potempa-Jeziorowska, Magdalena (Family Medicine & Primary Care Review, 2020)
Aspiration pneumonia usually occurs among infants with co-existing medical states like neurological, abnormalities of deglutition, gastroesophageal reflux or congenital malformations. In rare cases, aspiration can also be accidental among healthy children. In this group of patients, aspiration pneumonia develops less frequently because of properly working protective mechanisms. The author presents an 8-week-old baby with no-comorbidities that aspirated during sleep. Due to the Breathing Movement Monitor alarm and proper observer reaction, the baby was saved. Observation of aspiration pneumonia was negative. The paper also presents some theory about apnea and aspiration pneumonia in children.